Niewydolność nerek w przebiegu szpiczaka mnogiego = Renal failure in multiple myeloma - Surowiec, Agnieszka; Wołowiec, Łukasz; Kochański, Bartosz; Kałużna, Anna; Kałużny, Krystian; Krakowska, Alicja; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Surowiec Agnieszka, Wołowiec Łukasz, Kochański Bartosz, Kałużna Anna, Kałużny Krystian, Krakowska Alicja, Zukow Walery. Niewydolność nerek w przebiegu szpiczaka mnogiego = Renal failure in multiple myeloma. Journal of Education, Health and Sport. 2016;6(1):262-270. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45356 http://ojs.ukw.edu.pl/index.php/johs/article/view/3346 https://pbn.nauka.gov.pl/works/710506 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.01.2016. Revised 12.01.2016. Accepted: 31.01.2016. Niewydolność nerek w przebiegu szpiczaka mnogiego Renal failure in multiple myeloma Agnieszka Surowiec1,Łukasz Wołowiec2, Bartosz Kochański3, Anna Kałużna3, Krystian Kałużny3, Alicja Krakowska3,Walery Zukow4 1Studenckie Koło Naukowe Diagnostyki i Terapii Niewydolności Serca, II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2II Katedra Kardiologii, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 3Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Pierwszą manifestacją kliniczną szpiczaka mnogiego (MM) może być niewydolność nerek (z ang. renal failure RF). Podwyższone stężenie kreatyniny w surowicy jest już często obecne w momencie rozpoznania choroby aż u 20-50% pacjentów z MM. MM charakteryzuje się proliferacją monoklonalnych komórek plazmatycznych, wytwarzających białko M i rozwija się etapami. W pierwszym etapie komórki B stają się nieśmiertelne z powodu translokacji chromosomalnej w locus ciężkiego łańcucha immunoglobulinowego. Rokowanie u pacjentów z kreatyniny w surowicy> 2,0 mg/dl. Ponadto, pacjenci z niewydolnością nerek są często eliminowani z agresywnych czy też wysokodawkowych protokołów chemioterapeutycznych ze względu na ich toksyczność. Abstract One of the first symptoms of multiple myeloma (MM) can be renal insufficiency (RI). Elevated concentration of serum creatinine states is already present at the time of diagnosis in 20–50% of patients with MM. MM is characterised by monoclonal proliferation of plasma cells which are producing monoclonal immunoglobulin (M protein). The disease develops in many stages. In the first stage the cells B becomes immortal due to chromosomes translocation in the immunoglobuline heavy chain locus. The prognosis for patients with a serum creatinine >2.0 mg/dL is very bad. Moreover, patients with renal failure are often excluded from aggressive or high-dose chemotherapy protocols because of an expected higher toxicity rate. Słowa kluczowe: szpiczak mnogi, gammapatia monoklonalna, niewydolność nerek. Keywords: multiple myeloma, monoclonal gammopathy, renal failure.